87 Neutrophil dynamics following acute myocardial injury live in an embryonic zebrafish model. (June 2018) - Baghbadrani, Aryan; Bruton, Finnius; Tucker, Carl; Taylor, Jonathan
Abstract : Innate immune cells, particularly neutrophils, are the first responders following myocardial infarction (MI). During inflammation resolution, neutrophils undergo apoptosis contributing to a more reparative phenotype within the surrounding milieu. However, the function of neutrophils following MI is not well-defined. We hypothesise that inducing neutrophil apoptosis to resolve inflammation will enhance heart repair and regeneration following injury. We have developed a novel and reproducible model of acute cardiac injury by lasering the ventricle of embryonic zebrafish at 3 days post-fertilisation. Cardiomyocyte and neutrophil reporting zebrafish (Tg(myl7:GFP; mpx:mCherry)) were used to quantify the extent of heart injury, heart function and neutrophil dynamics live in vivo up to 48 hours post injury (hpi) by serial imaging using epifluorescent microscopy. Additionally, more sophisticated single plane illumination microscopy (SPIM) combined with optical gating technology is being used to image heart-neutrophil interactions at greater spatial and temporal resolution. Lasered embryos exhibit a loss of GFP at the ventricular apex. Percentage ventricular GFP lost increases and is most significant at 6hpi 3.75±0.635 compared to uninjured embryos (p<0.0001). This decreases by 48hpi 1.17±0.192 (p<0.5). Coincidentally, neutrophil chemotaxis to the wound site occurs by 2hpi, with the number of heart-associated neutrophils peaking at 6hpi 3.15±0.365 compared to uninjured embryos 0.1±0.069 (p<0.0001). This number decreases to baseline at 48hpi. Analysis of heart function revealed no significant change in heart rate at any time point after injury. However, ejection fraction was most significantly reduced at 2hpi 18.61±1.329 compared to uninjured embryos 22.72±0.535 (p<0.0001), which steadily recovers to baseline by 48hpi. Tracking heart-associated neutrophils at the same time points using SPIM revealed a similar dynamic trend. Furthermore, 24 hour time-lapse movies (where z-stacks were obtained every three minutes) confirmed the increase in ventricular GFP lost between 4–6hpi. Following this, we also observed bridging and budding of cardiomyocytes over the wound site, indicative of repair/regeneration. Combined, epifluorescent microscopy and SPIM data suggest cardiomyocyte death/dysfunction within 6hpi (concurrent with neutrophil association) and functional heart recovery/regeneration by 48hpi. The exact role of neutrophils during this reparative response still remains unclear and will be further investigated. Importantly, this zebrafish model will serve as a platform to perform pharmacological screens with the aim of identifying compounds that harness the resolution of neutrophilic inflammation and enhance heart repair and regeneration.